IL-6 and cfDNA monitoring throughout COVID-19 hospitalization are accurate markers of its outcomes - Salvador Bello; Ana Belén Lasierra; Lucía López-Vergara; Cristina de Diego; Laura Torralba; Pablo Ruiz de Gopegui; Raquel Lahoz; Claudia Abadía; Javier Godino; Alberto Cebollada; Beatriz Jimeno; Carlota Bello; et al. (Respiratory Research, 2023)
Abstract Background Severe COVID-19 entails a dysregulated immune response, most likely inflammation related to a lack of virus control. A better understanding of immune toxicity, immunosuppression balance, and COVID-19 assessments could help determine whether different clinical presentations are driven by specific types of immune responses. The progression of the immune response and tissular damage could predict outcomes and may help in the management of patients. Methods We collected 201 serum samples from 93 hospitalised patients classified as moderately, severely, and critically ill. We differentiated the viral, early inflammatory, and late inflammatory phases and included 72 patients with 180 samples in separate stages for longitudinal study and 55 controls. We studied selected cytokines, P-selectin, and the tissue damage markers lactate dehydrogenase (LDH) and cell-free DNA (cfDNA). Results TNF-α, IL-6, IL-8, and G-CSF were associated with severity and mortality, but only IL-6 increased since admission in the critical patients and non-survivors, correlating with damage markers. The lack of a significant decrease in IL-6 levels in the critical patients and non-survivors in the early inflammatory phase (a decreased presence in the other patients) suggests that these patients did not achieve viral control on days 10–16. For all patients, lactate dehydrogenase and cfDNA levels increased with severity, and cfDNA levels increased in the non-survivors from the first sample (p = 0.002) to the late inflammatory phase (p = 0.031). In the multivariate study, cfDNA was an independent risk factor for mortality and ICU admission. Conclusions The distinct progression of IL-6 levels in the course of the disease, especially on days 10–16, was a good marker of progression to critical status and mortality and could guide the start of IL-6 blockade. cfDNA was an accurate marker of severity and mortality from admission and throughout COVID-19 progression.